Literature review of teenage pregnancy in Uganda - Anena, Rachel Mary; Orishaba, Judith; Mwesigwa, David (Advances in Social Sciences Research Journal, 2020)
Teenage pregnancy is a serious social and health concern. The aim of the study, as a literature review, was to investigate the causes, effects and strategies put forward to curb down the teenage pregnancy among girls between 13-19 years in lira district, Uganda. This study used desktop research using secondary data. The data was collected by others for their own purpose and it had been derived from various sources. This entails the findings and discussion got from causes, effects and strategies put in place to curb down teenage pregnancy. Social factors include decreased supervision by parents, early initiation to sexual activities, and pressure from families to marry early. Effects of teenage pregnancy were found to be preterm labour, intrauterine growth, sexually transmitted infections, sexual violence and limited access to medical services. There are policies designed to delay and protect young women from becoming pregnant during adolescence. These policies include the National Health Policy, the National Adolescent Health Policy, the National Policy on Young People and HIV/AIDS, the Sexual Reproductive Health Minimum Package, the Minimum Age of Sexual Consent Policy the defilement law. These policies also serve the purpose of fostering a supportive environment to encourage adolescent reproductive health. Given the factors that contribute to teenage pregnancy and its associated effects, it is concluded that the measures proposed in form of policies will help to curb down the problem of teenage pregnancy in Lira district.